Modernizing the Surveillance Mandate and Modalities. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper reviews the status of financing for the Fund's concessional lending and debt relief activities for low-income countries (LICs). It is based on the latest available data and projections, and it takes into account the commitments made so far in response to the Managing Director's fund-raising request of August 2009. The paper is organized as follows. Section II summarizes: (i) the comprehensive reforms of the Fund's concessional lending instruments and the associated financing framework that have become effective since the last review; and (ii) the measures that the Board recently endorsed to facilitate the needed mobilization of loan resources. Section III on the financing of PRGT operations begins by reviewing the projected financing needs established in July 2009 in light of recent commitments under the PRGT, and then considers the status of loan and subsidy resources, before discussing developments in the PRGT Reserve Account. Sections IV and V provide updates on the subsidization of emergency assistance and the financing of debt relief under the HIPC and MDRI.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet